MENGGIRING “AKAD PERTAMA” DALAM HERMENEUTIK T.K. SEUNG - Silvia Rosa (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2018)
This paper discusses a short story entitled "Akad Pertama" written by a young author originating from West Sumatra, Zulfahmi. Discussion of this short story aims to provide interpretation of the signs contained in the short story "Akad Pertama", and make thematic interpretation of the short story. The language that becomes the medium of the literary work is full of signs and meanings that the reader needs to interpret. The wealth of signs and meanings keeps the cultural code the author sends to the reader. Hermeneutic research methods and the application of hermeneutic theory can open local cultural codes that authors use to convey their ideology. The results of the study show that the author wants to reject imitations of misguided lifestyles by the people in big cities.